2015
DOI: 10.5539/ijef.v7n8p53
|View full text |Cite
|
Sign up to set email alerts
|

Audit Structure, Time Pressure and Judgment Accuracy: A Comparison between Strategic System Audit and Traditional Audit

Abstract: The development of audit practice is a continuous process. The strategic system audit (SSA) method is a quite recent audit procedure that represents a complete shift from old audit techniques as it relies on assessing the client"s business risk using a top-down rather than a bottom-up (traditional) approach. Previous studies focused on the effectiveness of SSA in performing audit. In addition, previous studies did not rule out the role of auditors" experience in an experimental procedure that compares between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…This indicated that RC among academics engendered high levels of WT. Given that earlier studies by Tastan (2016) and Abuaddous et al (2015) found RC to have a positive impact on WT, it was not surprising that this study found RC to have a significant impact on WT.…”
Section: Regression Analysissupporting
confidence: 45%
“…This indicated that RC among academics engendered high levels of WT. Given that earlier studies by Tastan (2016) and Abuaddous et al (2015) found RC to have a positive impact on WT, it was not surprising that this study found RC to have a significant impact on WT.…”
Section: Regression Analysissupporting
confidence: 45%
“…Recent research such as Broberg at al. (2017) and Abuaddous et al (2015) also revealed the same result of a negative influence of time pressure on audit performance. However, Wijaya and Yulyona (2017) as well as Sacramento, Fay & West (2013) found that there is no association between time pressure and job performance.…”
Section: Time Pressurementioning
confidence: 61%
“…This can consequently affect the efficiency of the audit judgment (Pierce and Sweeney, 2004). Abuaddous et al (2015) show that time pressure when completing the audit task affects audit effectiveness. Thus, audit quality decreases when the audit firms put their staff on a limited time budget to complete the audit process.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%